Focus Group Discussion Pembuatan Peta Batas Wilayah Padukuhan di Kalurahan Kebonharjo, Kapanewon Samigaluh, Kabupaten Kulon Progo: Focus Group Discussion on Hamlet Boundary Mapping of Kebonharjo Village, Samigaluh District, Kulon Progo Regency - Fathurrohmah, Septiana; Kurniati, Ayu Candra (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Geospatial information has expanded widely, including development and regional aspects. Kebonharjo sub-district, which is in the Kapanewon Girimulyo administrative area, Kulon Progo Regency, is committed to participating in regional development by trying to optimize its various potentials. However, the database and profile of potentials (and problems) are still limited, need better documented, and are still limited to tabular data. The database and profile will have added value if presented with a spatial approach like a map. Community service programs were carried out to make a map as a basis for developing spatial data and profiles. In the preparation step, the agendas include discussion with the village official to scope the activities and products, downloading satellite image data as a basis for mapping, and collecting maps for initial reference for area boundaries. Next, the technical activities for making the map were started by carrying out the Focus Group Discussion with village officials and community representatives from all of the hamlets to obtain agreement on the boundaries of the hamlet and Rukun Tetangga (RT) areas. The results of the Focus Group Discussion were digitized and processed in the laboratory to obtain map products and an overview of public understanding regarding mapping. The output achieved from the community service was the Padukuhan and Rukun Tetangga Area Boundary Map products, both in printed and soft file versions.